Linearity Analysis of Source-Degenerated Differential Pairs for Wireline Applications - Yadav, Kunal; Hsieh, Ping-Hsuan; Chan Carusone, Anthony (IEEE open journal of circuits and systems, 2025)
This paper presents a comprehensive analysis of nonlinearities in differential pairs with source degeneration and their impact on wireline communication applications. We assess the suitability of three nonlinearity metrics to quantify the receiver analog front-end performance. This work identifies the primary sources of nonlinearity in differential pair circuits including, broadband Variable Gain Amplifiers (VGAs) and Continuous-Time Linear Equalizers (CTLEs) using circuit simulations. Furthermore, the linearity performance of different front-end configurations is evaluated, providing design insights. The analysis is validated through simulations with a 22-nm FDSOI technology.